Sustainable Development and its major policies in India - Simran Parveen (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
Public policy is a plan of a government to provide services, facilities and security to the common people for a longer period of time. In general laws and policies are meant to bring development and overcome the difficulties in the society. The Millennium development goals which was given by General Secretary of UNO, Kofi Anan in 2000 in his report “We the peoples: The Role of the United Nations in the 21st Century” focused on world developments to bring changes in the 21st century and shape it as advanced and fast moving century which continued 2015 with its full paced until Sustainable Development has not entered. The sustainable development goals has replaced the concept of Millennium development goals because of its positive support of environment protection and taking care of future generation. The largest democracy in the world also accepted the 17 goals of sustainable development in its domestic policies and plans to meet the needs of the future generation, which can be seen in several schemes such as Swachh Bharat Abhiyan, Beti Bachao Beti Padhao, Pradhan Mantri Awas Yojana, Pradhan Mantri Jan-Dhan Yojana, Deen Dayal Upadhyay Gram Jyoti Yojana and Pradhan Mantri Ujjwala Yojana. Niti Aayog, the successor of Planning Commission has taken up the charge to deals with all the progress of the States and Union territories related with developments and assigned them the ranks according to the progress report. This paper will deals with Laws, policies and development and then major focus on Sustainable Development as general and India as a specific with the overall development, obstacles and solutions.